2004
DOI: 10.1074/jbc.m406099200
|View full text |Cite
|
Sign up to set email alerts
|

The H+-pyrophosphatase of Rhodospirillum rubrum Is Predominantly Located in Polyphosphate-rich Acidocalcisomes

Abstract: Acidocalcisomes are acidic, calcium storage compartments with a H؉ pump located in their membrane that have been described in several unicellular eukaryotes, including trypanosomatid and apicomplexan parasites, algae, and slime molds, and have also been found in the bacterium Agrobacterium tumefaciens. In this work, we report that the H ؉ -pyrophosphatase (H ؉ -PPase) of Rhodospirillum rubrum, the first enzyme of this type that was identified and thought to be localized only to chromatophore membranes, is pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
90
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 47 publications
5
90
1
Order By: Relevance
“…However, in vivo data obtained with the H + -PPase from the proteobacterium Rhodospirillum rubrum were consistent with the capacity of this enzyme to play two distinct roles depending on location and conditions. It can act as an intracellular H + pump in the acidocalcisomes (Seufferheld et al, 2004) or a PP i synthase in the chromatophore membranes during illumination (Baltscheffsky et al, 1966). Bacterial H + -PPases share significant homology with their plant counterparts (Seufferheld et al, 2011).…”
mentioning
confidence: 99%
“…However, in vivo data obtained with the H + -PPase from the proteobacterium Rhodospirillum rubrum were consistent with the capacity of this enzyme to play two distinct roles depending on location and conditions. It can act as an intracellular H + pump in the acidocalcisomes (Seufferheld et al, 2004) or a PP i synthase in the chromatophore membranes during illumination (Baltscheffsky et al, 1966). Bacterial H + -PPases share significant homology with their plant counterparts (Seufferheld et al, 2011).…”
mentioning
confidence: 99%
“…The finding of enzymes and transporters in the surrounding membrane of these organelles was fundamental in understanding their potential function and origin, and these studies started after their description in trypanosomatid and Apicomplexan parasites (3,9,10). The discovery of acidocalcisome-like organelles in bacteria (11,12) and human platelets (13) suggested that the acidocalcisome is an organelle that either evolved before bacterial and eukaryotic lineages diverged (3) or appeared independently by convergent evolution. Recent work has shown that acidocalcisomes have similarities to lysosome-related organelles (LROs).…”
mentioning
confidence: 99%
“…The V-H + -PPase is an electrogenic proton pump that has so far been described in bacteria [26], microorganisms [8,40], plants (reviewed in [41]), and recently found in insects [42], being absent in mammalians. The H + -translocating pyrophosphatase activity characterized here was shown to be located in acidocalcisomes in accordance with previous results found in different trypanosomatids [39].…”
Section: Discussionmentioning
confidence: 99%
“…Acidocalcisomes are calcium-rich acidic organelles first described in Trypanosoma brucei [6] and Trypanosoma cruzi [12], and then in several other trypanosomatids such as Leishmania [10,13,14], Phytomonas [11,15], Herpetomonas [16], Crithidia, Blastocrithidia, and Leptomonas [17], in apicomplexan parasites such as Plasmodium [18,19] and Toxoplasma [20][21][22], in other unicellular organisms such as Chlamydomonas reinhardtii [23], Dictyostelium discoideum [24], and in the bacteria Agrobacterium tumefaciens [25] and Rhodospirillum rubrum [26]. Acidification of acidocalcisomes is promoted by a V-type proton ATPase (V-H + -ATPase) [27,28] and a V-type pyrophosphatase (V-H + -PPase) [8,10].…”
Section: Introductionmentioning
confidence: 99%